Fuzzy C-Means Clustering for Customer Segmentation - Pradipta, I Made Dhanan; Anwar Wahyudi, Agus Eka; Aryani, Sri (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
The right marketing strategy for a company can increase revenue for the company. A product will not be bought even known if the product sold is not clear its usefulness. Therefore, market segmentation is used to predict market demand based on market groupings such as Measurability (buyer characteristics and characteristics), Accestability (segmentation selected by company) and Substantiability (large segment and profitable to serve).Customer segmentation is used to determine the status of potential customers to choose the right market strategy for the company. Clustering method used is fuzzy c-means, this method is determined based on the existence of each data point by the degree of membership. Segmentation using this clustering method will generate customer labels such as superstar, golden, typical, occasional, everyday, and dormant.